Language learning strategy (LLS) verification of Oxford instrumentation in Arabic language learning: a comparative study of IIUM, UKM, UM and UPM - Haji Daud, Nadwah (s.n, 2012)
The Strategy Inventory Language Learning (SILL) is a popular instrument frequently used when researching language learning strategies. The present study adopted the instrument Version 7.0 and was treated on Arabic Language Learning at IIUM, UKM, UM and UPM. The instrument intends to measure the six basic components when learning language which are memory, cognitive, compensation, metacognitive, affective and social strategy. In this study, a sample of 224 university students who had experience the learning of Arabic language and attended Arabic language classes. A total of 50 questions were tested and each of question corresponded to one of the six dimensions. Scale validation through measurement model of SEM confirmed the relationship of sub-constructs. These six-factor orientations produced valid measurement model and it is suitable to be used to study the Arabic Language Learning Strategy.